Eco-Translatology in the Indonesian Translation of The Wild Robot - Silmi, Farhati Haqiya (NOBEL: Journal of Literature and Language Teaching, 2025)
Eco-Translatology, first introduced by Hu Gengshen in 2001, bridges the integrity of language and ecology in the translation process by drawing on linguistic, cultural, and communication dimensions. This study applies the Eco-Translatology approach to analyze the Indonesian translation of “The Wild Robot” by Peter Brown. Using a descriptive qualitative method, the writer discusses translation data items consisting of words, phrases, and sentences, based on the three dimensions of Eco-Translatology. The results of the analysis show that the translator actively adapts and selects the linguistic aspects to maintain the naturalness and readability of the target text. Meanwhile, the cultural dimension suggests a relatively balanced application of domestication and foreignization strategies in translating cultural and ecological specific terms. Finally, communicative dimensions reflect how the translator preserves meaning and intention within the discourse in the overall ecological adaptation of the translation. The study offers insight into the practical application of ecological translation principles in Indonesian translation contexts.